Pressing device for insulating sheet and pressure-sensitive adhesive - AO JIANFENG (2024)
The utility model relates to the technical field of mechanical tools, and discloses a pressing device for an insulating sheet and a pressure-sensitive adhesive. The pressing device comprises a workbench, a positioning jig, a pressing mechanism, a rolling mechanism and a moving mechanism, a supporting frame is arranged on the workbench, the positioning jig is arranged on the workbench and provided with a limiting groove, the pressing mechanism is arranged on the workbench, the moving mechanism and the rolling mechanism are arranged on the supporting frame, and the rolling mechanism is in transmission connection with the moving mechanism. The pressing device is controlled by the controller, the insulating sheet and the pressure-sensitive adhesive are sequentially placed in the limiting groove of the positioning jig, the pressing mechanism presses one end of the pressure-sensitive adhesive and one end of the insulating sheet, then the rolling mechanism presses the pressure-sensitive adhesive downwards, and when